2015
DOI: 10.1103/physreve.92.053009
|View full text |Cite
|
Sign up to set email alerts
|

Near-surface viscosity effects on capillary rise of water in nanotubes

Abstract: In this paper, we present an approach for predicting nanoscale capillary imbibitions using the Lucas-Washburn (LW) theory. Molecular dynamics (MD) simulations were employed to investigate the effects of surface forces on the viscosity of liquid water. This provides an update to the modified LW equation that considered only a nanoscale slip length. An initial water nanodroplet study was performed to properly elucidate the wetting behavior of copper and gold surfaces. Intermolecular interaction strengths between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 51 publications
3
58
0
Order By: Relevance
“…Other than that, the second approach makes a simplification that fixed water viscosity concept is assigned in both the interfacial area and bulk area. 41,49,50 Notably, water viscosity in the interfacial area is closely related to the action force exerted by pore surface, and that in the bulk area is the same with bulk-water in a macroscopic view, which is free of the influence induced by surface-water interactions. In my opinion, the second approach provides a reasonable and convenient pathway to address the issue, in which the simplification is based on a reliable physical phenomenon, that is, the action distance of pore surface is confined within interfacial area.…”
Section: Water Viscosity In the Elliptical Nanoporesmentioning
confidence: 99%
“…Other than that, the second approach makes a simplification that fixed water viscosity concept is assigned in both the interfacial area and bulk area. 41,49,50 Notably, water viscosity in the interfacial area is closely related to the action force exerted by pore surface, and that in the bulk area is the same with bulk-water in a macroscopic view, which is free of the influence induced by surface-water interactions. In my opinion, the second approach provides a reasonable and convenient pathway to address the issue, in which the simplification is based on a reliable physical phenomenon, that is, the action distance of pore surface is confined within interfacial area.…”
Section: Water Viscosity In the Elliptical Nanoporesmentioning
confidence: 99%
“…For the velocity at the walls, a no-slip boundary condition is used; for the nanoparticles concentration a no-flux boundary condition ensures that no particle is capable of penetrating the wall. It is worth pointing out that in nanofluidics the hydrodynamic slippage of the fluid is also possible due to the effect of the properties of the interface, such as wettability and roughness [29,35,37,84,85]. Table 1.…”
Section: The Expanded Forms Of the Governing Equations And The Boundamentioning
confidence: 99%
“…According to the review articles [31,32], the thermal conductivity and viscosity usually increase non-linearly in the function of nanoparticle volume concentration. For revealing the mechanism of the thermal and momentum diffusivity of nanofluids and the thermal/dynamic performance at the interface between the fluid and nanoparticles, many works based on experiments [33], theoretical analysis/modelling [6,33] and molecular dynamics simulations [34][35][36][37] have been performed. For example, some works indicated that the viscosity of the nanofluids is dependent on the nanoparticles concentration due to the apparently enhanced-viscosity of the base fluid near the solid surface caused by the surface force effects at small scales [29,35,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the traditional Navier slip length and the extrapolated slip length from Figure 2 are shear rate-independent, but what the traditional Navier boundary assumption fails to capture is the transition from the positive slip to the negative slip phenomena.This is understandable since the definition of the boundary slip velocity used to obtain the Navier slip length makes it always positive. However, for the -COOH functionalized surface, there is actually no molecular slip as shown in the velocity profile inFigure 2c, where the slip boundary is displaced into the water.Since the slip phenomenon is still mostly in the linear Navier boundary condition(Figure 4), we further calculate the Navier shear viscosity according to:48…”
mentioning
confidence: 99%